Resilient Communities and Context-Specific Policies: Shaping Urban Environments in Banjarmasin's Slum Areas - Syariah, Arfiani; Ratodi, Muhamad; Heryanti, Septia (EMARA: Indonesian Journal of Architecture, 2023)
This study examines Banjarmasin City's low-income slum residents' views and housing preferences. To fully grasp their lives is the goal. This study seeks to explore the numerous elements affecting these communities' residential decisions and objectives. Additionally, it investigates the viability of implementing setting-specific urban policies and interventions. Our study used systematic review and thematic content analysis. Our 16 sources included qualitative investigations, quantitative surveys,  and policy publications. Our study covers demographics, slum living, residential preferences, economic limits, health risks, and natural disaster susceptibility. This study highlights the resilience of the people, their desire for better housing, the economic constraints of informal employment, the health risks of inadequate sanitation, and their susceptibility to natural disasters. The study's use of ambitious goals and community-based solutions sets it apart from prior research. Access to work is also a major factor in residential preferences, especially in Banjarmasin. This study enhances our understanding of urban life in slums and emphasizes the need for situation-specific urban policy. Our research suggests community-driven projects have great potential, emphasizing the need for localized solutions. This work advances urban planning and development by allowing low-income communities to shape their own futures. Future research should examine the long-term consequences of localized initiatives and the scaling possibilities of community-driven development strategies in urban areas.